PREEKLAMPSIA DENGAN BERAT BADAN LAHIR RENDAH (BBLR) PADA IBU BERSALIN - Ni Hartati (Jurnal Gema Keperawatan, 2018)
One of the risk factors that cause birth of LBW is mothers who have preeklampsia. Mothers with preeclampsia will experience a trophoblastic cell abnormality resulting in decreasing blood flow to uteroplacenta, which causing placenta deficiency of nutrients and hypoxia which resulting the obstruction of fetus This study aims to determine the relationship of preeclampsia with the low birth weight (LBW) in Wangaya Hospital in 2018. The method was the analytic correlation with Retrospective approach. the research sample is taken from secondary data, medical records Wangaya preeclamptic patients in hospitals by using sampling techniques which the total of sampling were 164 samples which is analyzed by using chi-square with the result (value) p = 0.000 (p value 0.05) and Odds Ratio (OR) = 4.752. It can be concluded that there is a link preeclampsia with the birth of low birth weight (LBW). Mothers with preeclampsia are four times more at risk of having babies with low birth weight.